Predicting multijoint maximal eccentric and concentric strength with force-velocity jump mechanics in collegiate athletes - McClean, Z. J.; McKenzie, M.; Zukowski, M.; Foley, L.; Pasanen, K.; Herzog, W.; Nabhan, D.; Jordan, M. J. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Maximal muscle strength is often assessed with single-joint or repetition-maximum testing. The purpose of this study was to evaluate the reliability of countermovement-jump (CMJ) velocity-load testing and assess the relationship between CMJ velocity-load kinetics and concentric-isometric-eccentric multijoint leg-extension strength tested on a robotic servomotor leg press in trained athletes.